Effect of running speed on the foot-ground angle in heel strikers - Schwameder, H.; Wunsch, T.; Schatz, T.; Kröll, J. (International Calgary Running Symposium, August 14-17, 2014, 2014)
75-97% of long distance runners use a heel strike pattern [1, 2], whereas sprinters perform forefoot strikes [3]. It is not clear if and how heel strikers change the foot-ground angle (FGA) with increasing running speed, which leads to the purpose of this study. 16 male heel strikers performed two ramp tests on a treadmill (start: 3 m/s; step: 0.1 m/s every 5 s; end: 6 m/s). FGA, stride length and stride rate were analyzed using 2D video analysis (200Hz). Based on the FGA analysis two types of runners could be identified. Type I runners showed a positive FGA (heel strike) for all speed levels, with a stable FGA (21±1deg) till about 4.9m/s followed by a decrease to 8±5deg (n=12; Fig.1a). Type II runners changed from a positive FGA at low speeds to a negative FGA (forefoot strike) at high speeds, showing a rapid transition from a stable heel to a stable forefoot strike (n=4; Fig.1b). With increasing running speed both stride length and stride rate revealed a curvilinear increase with no significant differences between type I and type II runners. This study demonstrates that heel strikers use different strategies for adjusting the FGA to the increase of running speed with similar effects on spatio-temporal variables in both groups. 75% of the participants are type I runners showing a FGA course similar to previous research in overground running [4]. These findings are important for the shoe industry to support runners regarding performance enhancement, comfort and injury prevention.